Study on the Outdoor Comfort Threshold from Physical Loads: A Case Study in Biskra, Algeria - Qaoud, Rami; Alkama, Djamal (Technium Social Sciences Journal, 2023)
This study explores the values threshold of physical loads (air temperature, illumination, and sound level) applied in the urban space that represents the limits of human comfort, as well as the effect of the urban environment in terms of the density of buildings on those loads and help to provide ultimate comfort. The methodology of this study was founded on field experiments to obtain the physical load’s data for three consecutive days during the summer season’s peak. Then, this data is to be studied and analyzed through a comprehensive approach of the physical loads and according to the comfort levels of each load. The results proved the failure of the urban environment of the measurement stations to keep all the physical loads below the comfort threshold, except for the wind and sound loads that were below the comfort threshold. The air temperature and illumination were far from the comfort threshold, especially at midday and peak time. There were also differences in the values of the recorded loads between the measurement samples that reached a degree and a half for the air temperature, 8000 lux for illumination, and 7 dB for sound level. This remarkable difference explained the role of building density in the physical loads found in the open urban space, and the reduction of those loads to be within the required range of the physical comfort threshold.